Тhe legal regime of the Arctic – new challenges and dimensions (International relations and international law Journal, 2016)
The international legal regime of the Arctic with regard to the specifics of ice cover is based primarily on the UN Convention on the Law of the Sea since 1982. There is currently no military conflict for the possession of the territory, the demarcation of borders or the sea-bed. However, this does not exclude the possibility of a potential conflict in the near or distant perspective. The purpose of this paper is an analysis of the legal regime of Arctic, continental shelf, particular disputes on the establishment of boundaries between coastal waters, sovereign economic zones, continental shelves and the right to territorial sovereignty over the land in the Arctic.
Keywords: Arctic; the UN Convention on the Law of 1982; the Commission on the boundaries; exclusive economic zone; continental shelf